Evaluation and implementation of distance learning technologies, tools, and techniques - Belanger, France, 1963-; Jordan, Dianne H., 1950-; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2000)
The twentieth century has seen the creation and evolution of technologies beyond imagination a century ago. The computer has enabled the digital presentation of knowledge, and increased the speed with which information can be captured and processed. The acceptance of these technologies has led to a new alternative for providing education and training--distance learning. This book focuses on the processes, techniques and tools that are being used to successfully plan, implement and operate distance learning projects.
1. Introduction -- 2. Learning variables in distance learning -- 3. Distance learning technologies -- 4. Media conversion analysis and instructional design considerations -- 5. Multimedia content development -- 6. Distance learning implementation and evaluation -- 7. Examples of distance learning evaluation and implementation -- Appendicies.
Includes bibliographical references (p. 223-226) and index.
Also available in print.
Mode of access: World Wide Web.
Title from PDF t.p. (viewed on May 25, 2010).
Keywords: Distance education -- Computer-assisted instruction; Instructional systems -- Design; Educational technology; Electronic books